Perdón y salud mental en migrantes venezolanos (2021)
The violation of human rights in Venezuela as a result of the socioeconomic and political situation has brought with it the migration of millions of Venezuelans to Colombia, Riohacha being affected by being in a border region. Although it has been established in investigations in different countries such as those of Jurado et al. (2017), Gracia et al. (2009), Merino (2017), Ouarasse & Van de Vijver, (2005) on the effects that this phenomenon brings at a physical, psychological and social level, in Colombia there are no studies that account for the relationship of forgiveness in mental health of the migrant, which justified the need and convenience of conducting the investigation. That is why the present was aimed at establishing the relationship between forgiveness with satisfaction with migrant life, post-traumatic irrational cognitions and psychological well-being in Venezuelan migrants over 18 years of age living in the city of Riohacha. The research was developed with a non-experimental design of a correlational crosssectional type, where through a non-probabilistic convenience sampling, 200 Venezuelan migrants were selected in the city of Riohacha, of which 81% are women and 19% men, 40 % are between 26 and 40 years old, and 50% have between 1 and 3 years of having migrated; It should be noted that 53% of these are in an irregular situation in Colombia. The instruments used were: the Thompson Heartland forgiveness scale; the Diener Migration Life Satisfaction Scale, adapted by Neto & Fonseca; the Ryff psychological well-being scale and adapted by Díaz, Rodriguez, Blanco et al; and the inventory of post-traumatic cognitions by Foa et al. The results of the research show that there are significant correlations between the dimensions of forgiveness and psychological well-being, however, they do not exist with the other study variables, which is why it is stated that the latter are independent of each other. These can contribute to the construction of intervention strategies and programs that help respond to the humanitarian crisis in Colombia.